Morphological Response of Indigofera zollingeriana Mutant 2 Plants Irradiated with Gamma Rays in Coastal Areas - Sudarmanto , Aurelya Yulyanti; Nadir, Marhamah; Natsir , Asmuddin; Syahrir, Syahriani; Nasjum, Miftahul Reski Putra (Hasanuddin Journal of Animal Science (HAJAS), 2023)
Coastal areas are potential land for the cultivation of feed crops to support the availability of livestock forage. Indigofera zollingerianaplants have a high tolerance to salinity stress. Gamma irradiation technology, which can change the genetic structure of plants, is expected to increase plant tolerance. This study was conducted to determine the morphological response of Indigofera zollingeriana Mutant, two plants irradiated with gamma rays in coastal areas. This study used a complete randomized design (CRD) method with ten treatments and six replications. The treatments consisted of P0 (control/without irradiation); P1 (Indigofera M2 50 Gy); P2 (Indigofera M2 100 Gy); P3 (Indigofera M2 150 Gy); P4 (Indigofera M2 200 Gy); P5 (without irradiation + salinity stress); P6 (Indigofera M2 50 Gy + salinity stress); P7 (Indigofera M2 100 Gy + salinity stress); P8 (Indigofera M2 150 Gy + salinity stress); and P9 (Indigofera M2 200 Gy + salinity stress). The analysis of variance showed that different doses of gamma irradiation and salinity stress had a significant effect (P<0.05) on stem diameter and number of flowers of Indigofera zollingeriana plants. Irradiation dose of 150 Gy with salinity stress during seedling can grow higher leaves when planted in coastal areas. Keywords: Salinity Stress, Indigofera zollingeriana, Gamma Irradiation